Characterization of Impaired Cerebrovascular Structure in APP/PS1 Mouse Brains. (10th August 2018) - Ahn, Kee-Chan; Learman, Cameron R.; Dunbar, Gary L.; Maiti, Panchanan; Jang, Won-Cheoul; Cha, Hyeon-Cheol; Song, Mee-Sook
Highlights: Cerebrovascular impairment was observed in 5xFAD, an APP/PS1 mouse model of Alzheimer's disease (AD). The impaired blood–brain barrier (BBB) was indicated by the decreased expression of GLUT-1 and ZO-1. The breakdown of BBB integrity was associated with the activation of astrocytes in the progression of Aβ pathology. Abstract: Alzheimer's disease (AD) is defined by senile plaques, tauopathy and neuronal cell death in specific area of the brain. Recent studies suggest that neurovascular dysfunction may be an integral part of AD pathogenesis, contributing to the onset and development of AD pathologies such as neuronal death, inflammatory response, and breakdown of blood–brain barrier (BBB). In addition, vascular complications caused by age-related metabolic diseases such as diabetes and high blood pressure have high incidence in development of dementia and AD. We previously reported that astrocytes, essential components of BBB, were chronically activated and some deteriorated in the brain of 5xFAD, an amyloid precursor protein/presenilin1 (APP/PS1) transgenic mouse model. Thus, it is rational to investigate if any vascular dysfunction is associated with considerable activation of astrocytes in APP/PS1 mouse model. In this study, we observed that cerebrovascular pathology was associated with large scale of reactive astrocytes and neurodegeneration in an Aβ plague-generating mouse model. Using 5xFAD mouse brains, we demonstrate damaged brain vessels and reduced expression of glucose transporter 1 (GLUT1), the main glucose transporter, and a tight junction protein zonula occludens-1 (ZO-1) of cerebrovascular endothelial cells. This vascular pathology was closely associated with astrocytic deterioration and neuronal loss due to buildup of Aβ plaques in 5xFAD mouse brains.